Ecosystem uptake and transfer of Sellafield-derived radiocarbon (14C). Part 1. The Irish Sea. Issue 2 (30th January 2017) - Muir, Graham K.P.; Tierney, Kieran M.; Cook, Gordon T.; MacKinnon, Gillian; Howe, John A.; Heymans, Johanna J.; Hughes, David J.; Xu, Sheng
Abstract: Ecosystem uptake and transfer processes of Sellafield-derived radiocarbon ( 14 C) within the Irish Sea were examined. Highly variable activities in sediment, seawater and biota indicate complex 14 C dispersal and uptake dynamics. All east basin biota exhibited 14 C enrichments above ambient background while most west basin biota had 14 C activities close to background, although four organisms including two slow-moving species were significantly enriched. The western Irish Sea gyre is a suggested pathway for transfer of 14 C to the west basin and retention therein. Despite ongoing Sellafield 14 C discharges, organic sediments near Sellafield were significantly less enriched than associated benthic organisms. Rapid scavenging of labile, 14 C-enriched organic material by organisms and mixing to depth of 14 C-enriched detritus arriving at the sediment/water interface are proposed mechanisms to explain this. All commercially important fish, crustaceans and molluscs showed 14 C enrichments above background; however, the radiation dose from their consumption is extremely low and radiologically insignificant. Graphical abstract: Highlights: Ecosystem 14 C uptake and transfer processes examined for the Irish Sea All biotic components of east basin ecosystem near to Sellafield enriched in 14 C Significant 14 C enrichment observed in some western Irish Sea benthic organisms Organic sediments near Sellafield less enriched in 14 C than associated benthic species Feeding ecology and carbon integration period key in organism 14 C uptake